Effect of the ECAS. In adopting technology or seed potato growers in the field of agency agrarian – Ambo - Romero Matos, Simeón Genaro (2017)
This research was aimed to evaluate the effect of Agricultural Extension Strategy::School of Camp,in the training potato farmers for use as seed, in the process of strengthening its technologicalcapabilities and the adoption of techniques for obtaining greater crop productivity due to lack ofinformation in this sense that describes not only the methodological and strategic needs of the type“input intellectuals” to which must answer all agenda that has this purpose, taking into consideration,quantifiers parameters as yields per area, the quality of the harvested product and this coupled withthe degree of evolution of the strengths of their capabilities in the development of the educationalprocess of teaching - learning and achieve the expected results, since the programs or trainingprojects agricultural producers and especially for those who are engaged in seed production shouldrespond strongly to the unmet needs of users. The research was conducted considering that Targetpopulation was located in the districts of Chios, San Francisco Mosca and Maraypata Sector Ambodistrict and it was attended by professionals of Agrarian Agency Ambo and Program Pope seedlings,by the Organization for the united Nations Food and Agriculture - FAO, given that the premises wereconducted under irrigation. To carry out research a sample of 20 producers of seed potatoes of apopulation of 84, a situation which gave the respective scientific rigor auscultation. For informationgathering two types of surveys, one for members of the designated sample and another to collect the“Expert Opinion” to 10 professionals working in farming at the regional level were performed. Thesurvey questionnaire considered to capture the relevant information characterizing such producersas well as closely related to the purpose of the research, both of a technical nature - productiveas those concerning land management, the use of natural resources and those related to thebehavioral aspect, ie the psychic and social components. The method was exploratory, descriptiveand explanatory and it showed in detail the expected results, as the reader will appreciate to revisethis document was achieved formulated as a result of the investigation and that was the purpose ofthis (research). The conclusions that were reached show that all producers of seed potatoes, own,Usan certified seed with fertilizer application, perform proper sanitary control requirements as seedproducers, thus obtained expected returns and very acceptable averages; which allowed evaluatingthe Strategy: FFS if an instrument that promotes efficiency and effectiveness of training in seedpotato producers. Similarly, 100% of producers were satisfied with the development of the programand the work of technical assistance received from the Agrarian Agency Ambo, a situation that hasencouraged to raise pursue this program. To get something more in knowledge and practice.